The Impact of Tax Compliance on Future Certainty: A Simulative Artificial Intelligence Modeling of Optimization Portfolios - Muljanto Siladjaja (Jurnal Ekonomi dan Bisnis, 2026)
Tax compliance is proven as a quality measurement, indicating the majority probability of achieving future certainty without the possibility of total loss of investment returns, and it is a new indicator of no tax avoidance. Unambiguously, the dividend policy's signaling effect predicts future firm value: management tends to adopt a payout policy with high growth to take advantage of low-cost capital financing, which is associated with lower internal conflict intensity. The concept of the information usefulness of financial reporting has been tested using a multilevel, multiple-data-panel regression with a sample of 154 Indonesian manufacturing listed companies. This model includes a dummy variable reflecting high or low earnings quality as a guideline for highly prospective investment decisions. This statistical testing shows that investors have a favorable view of high compliance, with tax management designed to be more "prudent". The positive market price movement reflected the view that aggressive tax accruals had negatively affected investors' perceptions, and that adherence to accounting standards and tax compliance serves as a practical benchmark for assessing management's ethical decisions in illustrating real future earnings. In testing the rational decision-making process, the decision tree, Bayes' Theorem, and payoff matrix table provide supporting evidence for game theory, including artificial intelligence-based modeling to estimate firm value precisely, and illustrate the real future earnings as a constructive impact of positive earnings management. This payout policy should be established as a minimum standard to enhance transparency regarding future sustainability and serve as a valid indicator of expected returns.